TMEM164 promotes ferroptosis by selectively mediating ATG5-dependent autophagosome formation to inhibit the progression of LUAD - Yongxiang Su; Lintao Li; Junhai Chen; Chao Gao (Taylor & Francis Group, 2024)
The study focuses on lung adenocarcinoma (LUAD), a predominant type of lung cancer. Despite advancements in diagnostics and molecular therapies, treatment remains challenging due to its low five-year survival rate. This study aims to investigate the role of the transmembrane protein TMEM164 in ferroptosis and anti-tumor immunity in LUAD, and to evaluate its potential as a therapeutic target. Through cellular experiments (such as QPCR, WB, CCK-8, EdU, Transwell, flow cytometry, CO-IP) and animal model experiments (including HE staining and IHC analysis), the relationship between TMEM164 expression and LUAD progression was explored, with particular attention to its mechanisms in ferroptosis and autophagy. The results show that TMEM164 expression is downregulated in LUAD and is associated with poor prognosis. Increasing TMEM164 expression significantly inhibits cell proliferation, migration, and invasion, while promoting an autophagy process dependent on ATG5 for autophagosome formation, thus facilitating ferroptosis. In mouse models, high TMEM164 expression combined with anti-PD-1 antibodies demonstrated synergistic anti-tumor effects. These findings highlight the critical role of TMEM164 in LUAD, suggesting that modulating TMEM164 expression could open new avenues for LUAD treatment.